A Brief Study of Children’s Literature by Devkota - Khadka, Kul Bahadur (Journal of Development Review, 2021)
Great Poet Laxmi Prasad Devkota has written outstanding works like Muna Madan. Heremains immortal by virtue of his literary works. He has written for all, including children. Devkota’s children’s literature is very delightful, didactic, inspirational and philosophical. He has written lots of poems to delight and educate children. In this study, mainly his Raj Kumar Prabhakar, Putali and Sunko Bihan have been appreciated and analyzed. The study explores some major themes in the aforesaid poems and further makes a quest for the poet’s concern about children. The article structurally contains the introductory part, the poet’s works on children’s literature, the appreciation of his major works and the concluding arguments. In order to strengthen the appreciations and analyses of the poems, the poet’s his own works and the works and criticisms by various writers and critics have been consulted. Some striking opinions of critics have been cited. Children’s literature by Devkota teaches children to learn values, roles and lessons. It highly energizes them to be considerate to others. The poet wants children to embrace nature. He focuses on love for the country. He educates them to lead a hopeful, happy, disciplined and innovative life.